PENGARUH KONSENTRASI KALIUM NITRAT PADA MEDIA VERMIKOMPOS TERHADAP KANDUNGAN HARA DAN TRUBUS SELADA (LACTUCA SATIVA L.) - NAMSERNA, H. J. (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011))
The Effect of Potassium Nitrate Concentration in Vermicompost Medium on Nutrients Content and Shoot of Lettuce (Lactuca sativa L.) The content of nitrogen and potassium in vermicompost generally low, i.e. less than two percent, so that still require the addition of another source to meet crop requirement. Potassium nitrate to form the ions K+ and NO3 6 after disolved in water so as to be readily available to plants. The study aims to determine the effect of the addition of potassium nitrate in the growth medium made from vermicompost to increase growth lettuce plant and know the critical level of concentration or nutrient solution electrical conductivity with the addition of potassium nitrate to the lettuce plant. Research conducted in the form of pot experiment. Experiment using Randomized Complete Block Design (RCBD) with three replications. The treatment consists of 12 levels of concentration or nutrient solution electrical conductivity with the addition of potassium nitrate. The results of experiment indicated that addition of KNO3 highly significant effect on the increasing in fresh and dry weight of shoot per plant. Fresh and dry weight of shoot per plant were significantly increased in a quadratic with increasing concentrations of KNO3. The concentration of KNO3 are optimum for growth of plant shoot weight was at 12.23 g in 100l of water or electrical conductivity equivalent to 2.01 dS.m-1. The concentrations of P and K in plant shoot tissue were significantly increased linearly with the provision of KNO3. The concentration N, Ca, Mg, S, Na, Fe, Mn, Cu, Zn, Al and B in shoot tissue of plants is not affected KNO3.
Keywords: potassium nitrate, vermicompost, electrical conductivity, lettuce.